Study Concurrent Validity Antara script Consordance Test (SCT dan Multiple Choice Questions (MCQ) dalam Menilai Penalaran Klinik Mahasiswa Kedokteran - Yeny Dyah Cahyaningrum; Gandes Retno Rahayu; Efrayim Suryadi (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2016)
Background: In the teaching process at medical faculty, there are many measuring devices have been used to evaluate the clinical reasoning ability. Each measuring device has the advantage and disadvantage. MCQ and SCT are the clinical reasoning measuring device. In the previous study, both methods have been validated. SCT is a more recent method to measure clinical reasoning compared to MCQ. This study aims to evaluate the concurrent validity between MCQ and SCT.Method: Forty-three students who had already passed the Paediatric clinical rotation were asked to complete 100 items of MCQ. The next day, they did 100 items of SCT. The concurrent validity is measured using correlation analysis.Results: Concurrent validity between MCQ and SCT did not show strong correlation (coefficient of rank spearman correlation= 0.291 with the probability = 0.058).Conclusion: Concurrent validity between MCQ and SCT do not have strong correlation in evaluating the clinical reasoning. SCT is used as complement to evaluation of clinical reasoning in order to be more specific and close to real setting.